1998
DOI: 10.1046/j.1471-4159.1998.70052216.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulators of G Protein Signaling: Rapid Changes in mRNA Abundance in Response to Amphetamine

Abstract: This study examined mRNAs encoding regulators of G protein signaling (RGSs) expressed within the striatum and determined whether their expression in the caudate putamen was altered by amphetamine. RT‐PCR techniques were used to clone cDNA probes of RGSs expressed within the rat striatum. Northern blot analysis of caudate putamen and nucleus accumbens RNA determined the relative abundance of RGS mRNA expressed within the caudate putamen and adjacent nucleus accumbens to be RGS 2 > RGS 5 > RGS 16 > RGS 4 = RGS 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 15 publications
5
74
0
Order By: Relevance
“…We have found that rats exposed to PCP show attenuated D 4 inhibition of NMDAR current as a result of the loss of D 4 regulation of Ca 2ϩ /camodulin-dependent protein kinase II and unchanged D 1 enhancement of NMDAR current (Wang et al, 2006). Levels of RGS proteins or mRNAs are tightly regulated by neuronal stimuli, which provides an important mechanism for influencing GPCR signaling pathways (Burchett et al, 1998;Ingi et al, 1998). The specific alteration of RGS4 expression in PFC, a prominent area affected in schizophrenia (Weinberger et al, 1986;Andreasen et al, 1997), hints that RGS4 in PFC neurons may have specialized roles in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that rats exposed to PCP show attenuated D 4 inhibition of NMDAR current as a result of the loss of D 4 regulation of Ca 2ϩ /camodulin-dependent protein kinase II and unchanged D 1 enhancement of NMDAR current (Wang et al, 2006). Levels of RGS proteins or mRNAs are tightly regulated by neuronal stimuli, which provides an important mechanism for influencing GPCR signaling pathways (Burchett et al, 1998;Ingi et al, 1998). The specific alteration of RGS4 expression in PFC, a prominent area affected in schizophrenia (Weinberger et al, 1986;Andreasen et al, 1997), hints that RGS4 in PFC neurons may have specialized roles in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we found a significant increase in the midbrain RGS2 and RGS4 mRNA levels 18 h following 5 days of AMPH self-administration. Reports on RGS2 mRNA levels following non-contingent AMPH treatment have not been consistent with no change (Burchett et al, 1998) and an increase (Seeman et al, 2007) owing to different lengths of AMPH treatment and withdrawal. These data suggest that AMPH modulates RGS2 mRNA levels in a brain region-dependent manner.…”
Section: Amph Self-administration Selectively Promoted Membrane Transmentioning
confidence: 93%
“…It shows morphine-insensitive upregulation in a model of neuropathic pain (Garnier et al, 2003) and is reduced in schizophrenia (Mirnics et al, 2001). The acute or repeated administration of amphetamine promotes selective changes in striatal RGS-R4 mRNA levels (Burchett et al, 1998(Burchett et al, , 1999. Agonists and antagonists at D1 and D2 dopamine receptors also bring about changes in the level of this RGS4 mRNA (Robinet et al, 2001a, b;Geurts et al, 2002;Taymans et al, 2003).…”
Section: Introductionmentioning
confidence: 99%